MENINGKATKAN KETERAMPILAN BERCERITA MENGGUNAKAN METODE SHOW AND TELL PADA PELAJARAN BAHASA INDONESIA KELAS IV SDN KEBON KOSONG 17 - Raihan Suhailah Fadjrin; Gusti Yarmi; Dudung Amir Soleh (STKIP Subang, 2026)
Storytelling is an essential language skill that should be developed among elementary school students. However, observations conducted in Grade IV D of SDN Kebon Kosong 17 revealed that students' storytelling skills were still low. This study aimed to improve students' storytelling skills through the implementation of the Show and Tell method. The study employed CAR based on the Kemmis and McTaggart model, conducted in two cycles with 26 fourth-grade students as the participants. Data were collected through storytelling performance tests, observations, interviews, and documentation, and were analyzed using descriptive quantitative and qualitative methods. The findings showed that the implementation of the Show and Tell method improved students' storytelling skills. Therefore, the Show and Tell method is effective for improving storytelling skills in Indonesian language learning at the elementary school level.